ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA KELAS III DALAM MENYELESAIKAN SOAL KONTEKSTUAL DI SDN SUKAGALIH 1 - Rifa Melinai, Rifa; Rahman, Muklis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the numeracy literacy skills of third-grade students in solving contextual mathematical problems at SDN Sukagalih 1. This research employed a quantitative approach with a descriptive survey method. The subjects consisted of 20 third-grade students. The instrument used was a numeracy literacy test consisting of multiple-choice and short-answer questions based on real-life contexts. Data were analyzed using descriptive statistics, including mean, median, mode, and standard deviation. The results showed that the average numeracy literacy score was 59.95%, which falls into the moderate category. The distribution indicated that 45% of students were in the high category, 25% in the moderate category, and 30% in the low category. These findings suggest that students' numeracy literacy skills are not yet optimal, particularly in solving multi-step and contextual problems. Therefore, improvements are needed through contextual and problem-based learning approaches.